Mediterranean temporary ponds (habitat type 3170*) in the South Aegean Archipelago islands (Greece): filling the gaps - Karadimou, E.; Kemitzoglou, D.; Tsiaoussi, V. (2023)
Karadimou E., D. Kemitzoglou, and V. Tsiaoussi. 2023. Mediterranean temporary ponds (habitat type 3170*) in the South Aegean Archipelago islands (Greece): filling the gaps. Poster presentation in the Symposium for European Freshwater Sciences (SEFS 13), Newcastle University, England, 18 -23 June 2023.